Strategies to improve the argumentative competence in university students - Cardozo Rincón, Gerardo; Barrios Andrade, Diego Fernando (Rastros Rostros, 2021)
This article presents some strategies related to the improvement of the argumentative competence in university students. The objective was to improve the students’ abilities through some organized activities. Takinginto account the characteristics of this study, this is an action research. The population was the students of theUniversidad Santo Tomás, sectional Tunja. The results show the aspects related to argumentative speechesdone by the students based on their participation in the activities. Lastly, the conclusions present generalinformation found in the final argumentative discourses; it was determined that the activities were effectivebecause the last discourses included valid arguments; because of the speeches were presented orally, it wasdistinguished the importance of paralanguage in the presentations.
Keywords: argumentation; thesis; types of arguments; pragmatics